Microbiota and oral disease - Cvitkovitch, Dennis (Henry Stewart Talks, 2011)
Oral health reflects overall heath, Ecological imbalance leads to disruption of oral flora, Leads to dental caries (cavities), gingivitis and periodontitis
Reviewed at 2016/02/08